KUALITAS VISUM ET REPERTUM PERLUKAAN DI RSUD BANGKINANG PERIODE 1 JANUARI 2009 - 31 DESEMBER 2013 - Ghifari, Annisa Abdi; Afandi, Dedi; Chandra, Fifia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTIn addition to treat patients , a doctor’s duty is also requested to make a written statement for justice importance that is called Visum et Repertum (VeR). VeR of injury for living victims is the most frequent form of assistance requested by investigating officers compared to other kinds of VeR. A good quality of VeR is required in view of its important role in litigation of a criminal offense. This study was aimed to understand the quality of VeR of injury in General Hospital of Bangkinang during 1st January 2009-31st December 2013. The research was an observational study using descriptive retrospective design. This study used Herkutanto’s scoring method towards 13 VeR substances. Samples of this study were all data of VeR of injury that had fulfilled inclusion criteria. The total of samples were 316 samples of VeR. This study suggested that the highest number of living victims of injury cases was 191 victims in age group 22-40 years old with the most frequent sex was male as many as 117 victims. The most frequent violence was blunt violence as many as 266 cases with the most frequent age group was 22-40 years old. The quality of VeR in preface was good quality, in body part was poor quality and in conclusion was medium quality. In general, quality of VeR of injury in General Hospital of Bangkinang during 1st january 2009-31st december 2013 was 50,93% that could be categorized as medium quality.Keywords: Visum et Repertum, injury, quality of VeR of injury